Incidence, Predictors, and Management of Femoral Vascular Complications Following Catheter Ablation for Atrial Fibrillation: A Systematic Duplex Ultrasound Study - Hyo Jin Lee; Su Hyun Lee; Seongjin Park; Myoung Jung Kim; Juwon Kim; Ju Youn Kim; Seung-Jung Park; Young Keun On; Kyoung-Min Park (Biomedicines)
Background/Objectives: Catheter ablation is an effective treatment for atrial fibrillation (AF) but is associated with femoral vascular complications. While anticoagulation therapy has been linked to these complications, specific risk factors remain unclear. This study assessed the incidence and predictors of vascular complications after catheter ablation using systematic duplex ultrasound (DUS) as well as their outcomes. Methods: A single-center observational study was conducted with 404 consecutive AF patients who underwent catheter ablation between March 2023 and February 2024. DUS was performed systematically post-procedure in all patients to identify complications; these were primarily treated with DUS-guided manual compression. Results: Vascular complications were observed in 6.4% of patients, higher than reported in previous studies. Hematomas (3.5%) and arteriovenous fistulas (AVFs, 2.0%) were the most common such complications. Multivariate analysis identified repeat ablation (odds ratio [OR] 3.09, 95% confidence interval [CI] 1.10–8.64, p = 0.03) and months of experience <6 months (OR 3.42, 95% CI 1.36–8.63, p = 0.01) as significant predictors of complications. DUS-guided compression managed most complications successfully, with three pseudoaneurysms resolved through compression and one through embolization. However, AVFs were relatively resistant to conservative management, often necessitating prolonged observation or intervention. Conclusions: Systematic DUS following catheter ablation revealed a higher-than-expected incidence of vascular complications. Repeat ablation and months of experience <6 months are potential predictors of femoral vascular complications. DUS-guided compression is effective for most complications, although AVFs present greater treatment challenges.